KEPUTUSAN PEMBELIAN PRODUK ‘ONLINE TRAVEL AGENT’ OLEH WISATAWAN CINA - Mamanua, Riezchy Riando; Wirawan, I Gede Putu; Dewi, Made Heny Urmila (Jurnal Master Pariwisata (JUMPA), 2017)
Online travel agent (OTA) Cina offers variety of tourism products. However, some of tourism products that offered by OTA through website seem not interesting for Chinese tourists. This research aimed to analyze factors that influence for the Chinese tourists consumer on the decision of buying tourism product in Bali through OTA. This research was conducted in Bali island, the number of samples taken was 100 Chinese tourists who has bought tourism product in Bali through OTA by using quota sampling technique. Data was analyzed with exploratory factor analysis. Results show there are five factors that influence for the Chinese tourists consumer on the decision of buying tourism product through OTA namely Product, OTA, Reference Group, Tourist Characteristic and Income. Finally,this study identify that factor product is the most influence for the Chinese tourists on the decision of buying OTA product.